Increasing Fintech Literacy and Investment in Indonesia's Capital Market for Educators in Supporting Community Welfare in Palembang City - Hidayat, Ariodillah; Suhel; Liliana; Yunisvita; Andaiyani, Sri; Nida, Rahma; Shodrokova, Xenaneira (Universitas Nahdlatul Ulama Surabaya, 2025)
This service was held to improve financial literacy in technology (fintech), finance, and understanding of capital market investment for educators at Dharma Bhakti Junior High School, Palembang City, South Sumatra. The target of this activity is as many as 33 teachers who participate in the training and counseling program which includes the provision of financial literacy materials, fintech, investment practices in the capital market, and at the end of the activity there is an evaluation through filling out a questionnaire. The methods used in this service include interactive education sessions, investment practices using simulation applications, and group discussions to deepen participants' understanding. The results of this activity showed a significant increase in the level of financial literacy, introduction to fintech, and the ability to invest in the capital market by educators. This service shows a better understanding of capital market concepts, investment risks, and diversification strategies, which are expected to be applied in daily life as well as disseminated to students and the community by educators. Thus, this program has succeeded in achieving its goal of empowering educators as agents of change in improving financial literacy and inclusion.